2017
DOI: 10.1017/ice.2017.167
|View full text |Cite
|
Sign up to set email alerts
|

A Model to Predict Central-Line–Associated Bloodstream Infection Among Patients With Peripherally Inserted Central Catheters: The MPC Score

Abstract: BACKGROUND Peripherally inserted central catheters (PICCs) are associated with central-line-associated bloodstream infections (CLABSIs). However, no tools to predict risk of PICC-CLABSI have been developed. OBJECTIVE To operationalize or prioritize CLABSI risk factors when making decisions regarding the use of PICCs using a risk model to estimate an individual's risk of PICC-CLABSI prior to device placement. METHODS Using data from the Michigan Hospital Medicine Safety consortium, patients that experienced PIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 48 publications
5
71
0
Order By: Relevance
“…PN requires the use of peripherally inserted catheters, which can increase the probability for infection. PN therapy has been demonstrated to be a significant independent risk factor for central line–associated bloodstream infections . Studies have reported adult trauma patients receiving enteral feeding have fewer incidents of line sepsis, intra‐abdominal abscesses, pancreatitis, and other infections compared with patients receiving PN .…”
Section: Mucosal Atrophy Central Line Infection–driven Liver Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…PN requires the use of peripherally inserted catheters, which can increase the probability for infection. PN therapy has been demonstrated to be a significant independent risk factor for central line–associated bloodstream infections . Studies have reported adult trauma patients receiving enteral feeding have fewer incidents of line sepsis, intra‐abdominal abscesses, pancreatitis, and other infections compared with patients receiving PN .…”
Section: Mucosal Atrophy Central Line Infection–driven Liver Injurymentioning
confidence: 99%
“…PN therapy has been demonstrated to be a significant independent risk factor for central line–associated bloodstream infections . Studies have reported adult trauma patients receiving enteral feeding have fewer incidents of line sepsis, intra‐abdominal abscesses, pancreatitis, and other infections compared with patients receiving PN . The lack of enteral feeding further contributes to intraluminal bacterial overgrowth (notably, gram‐negative Proteobacteria) due to decreased intestinal motility and change in nutrition availability .…”
Section: Mucosal Atrophy Central Line Infection–driven Liver Injurymentioning
confidence: 99%
“…From the previous studies, the incidence of PICC-related complications was relatively high and the two most common complications were infection and catheter-related thrombosis in patients with hematological malignancies, however, we still could not conclude an accurate incidence range of complications due to the incidence of complications varies considerably with the number reported in each literature (from 3% to 61.67%). Hematopoietic cell transplantation (HCT) status [9], HM [17], type of disease [14], PICC type [9,17], sex [9], patient safety and hospital resources [17,18] were proved to be influencing factors. However, not all the literatures has reported the influencing factors, so we can't draw a conclusion.…”
Section: Incidence and Risk Factors Of Picc-related Complicationsmentioning
confidence: 99%
“…Third, we surveyed 30 patients who received the consent process for the PICC procedure The questionnaire used for knowledge recall and knowledge retention was created based on recent guidelines for PICC [22][23][24][25][26][27][28][29][30][31][32] and included 3 "select one-answer" multiple-choice questions, 4 "select all that apply" multiple-choice questions, and 12 true/false questions. The knowledge recall questionnaire was administered within 4 -8 hours after the discussion between the vascular access team nurse and the patient and obtaining the signed consent.…”
Section: Patients' Perceptions About the Current Processmentioning
confidence: 99%